Young children's emergent science competencies in everyday family contexts: a case study. Issue 8 (3rd July 2019) - Andrews, Kathryn J.; Wang, X. Christine
ABSTRACT: To address the lack of research in early science learning and young children's informal science experiences, this exploratory case study investigated a 7-year-old girl's (Abigail) emergent science competencies and how they are related to her science experiences in everyday family contexts. Data sources included observations, interviews, parent journals, and the child's digital journals that were collected over six months. Open-ended coding and constant comparison were used to analyse data. Findings revealed that Abigail's emergent science competencies were naïve but playful and included a developing, but sophisticated, understanding of the nature of science; family learning included both spontaneous and purposeful learning that contributed to her naïve theories and islands of expertise; and her mother's scaffolding played an important role in her emergent science competencies. The study suggests ways to connect formal science learning with informal science engagement to further young children's science competencies.